Bulgarian Film Industry: "Sun and Shadow" of the Transition. Markets, Policies, Deficits - Tomova, Bilyana (Research Papers, 2015)
Object the present study is the Bulgarian film industry, the subject of the analysis are the crises in its genesis during the transition. The main research hypothesis is that crises have a form of market and non-market failures, and are a reflection of the specificity of the product, the national cinema market and cultural policy during the period under review. And part of the defects are a reflection of the global crises of the emergence of new business models related to digitalization.In the course of the study outlined the paradox in the Bulgarian film industry: a serious economic contribution of macro level (value added, employment, number of firms), in combination with the instability of micro producer companies and monopolized and integrating markets of distribution and exhibition. As a result-limited access of the audience and the low efficacy of film production.Output from this harrowing development through crises are transformations-transformations to new business models through new sectorial policies.